Pengembangan Sistem Aplikasi Penentuan Prioritas Kasus Uji Berbasis Lexicographical Ordering - Lailatul Rizqi Ramadhani; Bayu Priyambadha; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Test case prioritization is a strategy of regression testing. It can reduce the cost of regression testing. Test case prioritization based on lexicographical ordering is considered to be the best technique based on its Average Percentage Fault Detection (APFD). This technique determines test case prioritization based on coverage information of each test case. There have been no studies that implement this technique into a system and research shows that prioritizing test cases based on code coverage is expensive both in terms of time and resources. Because the more number of test cases, the greater size of the code coverage information that have to be read. Therefore, this study developed an application system for test case prioritization based on lexicographical ordering. This system aims to help the process of reading coverage information and determining test case prioritization automatically. So this system is expected to accelerate the determination of test case prioritization. The results of testing phase show that the system has 100% accuracy with reading coverage information in each test case also finding prioritization in less than 8 seconds. This paper will summarize the application system development process. The stages described from the introduction, research methodology, results and discussion, and getting conclusions from the research.